Non-calcifying and Langerhans cell-rich variant of calcifying epithelial odontogenic tumor - Hung-Pin Lin; Ying-Shiung Kuo; Yang-Che Wu; Yi-Ping Wang; Julia Yu-Fong Chang; Chun-Pin Chiang (Elsevier, 2016)
This study reported the clinicopathological features, treatment and prognosis of nine cases of noncalcifying and Langerhans cell (LC)-rich calcifying epithelial odontogenic tumor (CEOT) collected from the English literature. Of the nine cases, seven were intraosseous and two were extraosseous. All nine tumors were found in Asian patients. The age of the nine patients ranged from 20 years to 58 years with a mean age of 41 years. There were five female and four male patients. The seven intraosseous cases included six in the anterior and premolar region of the maxilla and one in the posterior region and ascending ramus of the mandible. The two extraosseous cases were located at the upper lateral incisor and premolar gingivae, respectively. Of the seven intraosseous cases, five showed unilocular and two multilocular radiolucency without foci of calcification. Six of the seven intraosseous cases showed resorption of the tooth roots in the tumor-involved region. Histologically, noncalcifying and LC-rich CEOTs were composed of small nests and thin strands of tumor epithelial cells with a relatively high number of LCs among them. This was the reason why we classed these nine cases as noncalcifying and LC-rich CEOTs. Two extraosseous cases received total excision of the gingival mass. For the seven intraosseous cases, four accepted partial maxillectomy or mandibulectomy, two received total excision or enucleation, and one underwent curettage. The six cases with the follow-up information available showed no tumor recurrence after a follow-up period of 6 months to 10 years.